Synthesis of Magnesium Dicarboxylate Complex - Yunita, Isti; Somsook, Ekasith (Universitas Negeri Semarang, 2020)
The synthesis of magnesium dicarboxylate complex were completed and the coordination chemistry of magnesium dicarboxylate was investigated in the different pH under hydrothermal or solvothermal processes. It was proven that the synthesis conditions affected the shape of the compound due to the nucleation process, but had no effect on the functional groups of the synthesized compounds. Complex compound was characterized by Nuclear Magnetic Resonance (NMR), Electrospray ionization (ESI-MS), and Fourier transform-infrared spectroscopy (FT-IR).